MEASURING THE INFLUENCE OF DIRECT, CODED, UN-CODED FEEDBACK IN L2 WRITING ABILITY - Sarip, Jhon; Sabarun, Sabarun (Universitas Negeri Semarang, 2023)
The research investigated the influence of direct, coded, and un-coded feedback on the setting of writing class. The design was pre-posttest quasi experimental. The learners involved were 82 students at Islamic higher education in Kalimantan. The data were calculated using ANOVA test. The finding revealed that: (1) Direct Corrective Feedback (DCF) gave effect toward writing ability. The mean difference (MD) between DCF and NF was 16.86429* and the significance value was 0.00 0.05. (2) Indirect Coded Corrective Feedback (ICF) gave an influence on writing ability. The MD between ICF and NF was 12.72895* and the significance value was 0.00 0.05. (3) Indirect Un-coded Feedback (IUF) gave influence on writing ability. The MD between IUF and NF was 13.60455* and the significance value was 0.00 0.05. (4) The types of feedback (DCF, ICF, and IUF) gave an influence on writing performance at the p 0.05, and the F value (3, 78) = 30.38, p= 0.00). Tukey HSD test confirmed that the mean scores of the three kinds of feedback differed significantly from no feedback class. However, the different types of feedback did not differ significantly from either group 1, 2 or 3.